ANALISIS KETERAMPILAN SOSIAL PUSTAKAWAN DI UPT PERPUSTAKAAN UNIVERSITAS LANCANG KUNING - Purwanto, Ari (Program Studi Ilmu Perpustakaan, Fakultas Adab dan Ilmu Budaya, UIN Sunan Kalijaga Yogyaka, 2023)
Social skills are an individual's ability to interact effectively with others in various social situations. These skills encompass how a person communicates, understands, and responds to their needs, emotions, and actions of others in a positive and constructive manner. The purpose of this study was to determine the social skills of librarians at the Library Service Unit of Lancang Kuning University. This research employs a qualitative descriptive method, with the subjects were librarians and library users at the UPT of Lancang Kuning University. The result show that librarians already have good social skills as seen from how librarians respond to librarians who enter wihout following the rules in the library, such as carriying bags into the circulation room, noisy visitors, visitors who bring food and drinks, and users who repeatedly committing mistakes. Furthermore, librarians are willing to listen to users even while engaged in other tasks, addressing their complaints, and understanding their needs. Friendly attitude facilitates effective communication between librarians and the users. Additionally, librarians were capable of delivering verbal statements, such as setting boundaries and actively listening, as well as employing non verbal communication, including facial expressions, hand gestures, vocal intonation, and a professional appearance, to create responsive and communicative interactions.